(untitled) (Current Problems in Rail Vehicles, 2025)
This paper describes the benefits of semi-active control of lateral and vertical secondary dampers under real conditions on a Škoda 10Ev (“InterPanter”) EMU in comparison with conventional passive dampers. The results show a significant increase in ride comfort thanks to the semi-actively controlled dampers, especially at higher speeds and on poorer quality tracks. The mean comfort index (NMV) on standard lines is reduced by 26% on average according to EN 12299.